A coordinate vector correction method to improve the traditional affine transformation graphic digitised cadastral map. Issue 332 (September 2013) - Kao, S-P; Tu, C-P; Chen, C-N
Abstract : Parameter coordinate transformation regards the whole transformation region under the same condition for coordinate adjustment. However, the practical errors and ideal corrected values are not 'individually' discussed. The proposed coordinate vector correction method uses 'area' and 'point' to further correct individual coordinates in order to amend the blind spots resulting from overall coordinate transformation. The experimental areas in this study were five graphic area sectors in Taichung City. The graphic digitised TWD67 coordinate system was converted using affine transformation into the TWD97 coordinate system. The coordinate vector correction method was used to correct various boundary point coordinates. The results were compared with affine transformation results and analysed. According to the data obtained from the experimental areas, when the traditional affine transformation was used, the root-mean-square error value of the converted and registered areas could be reduced by 6–69% by using the proposed coordinate vector correction method. The quantity of land parcels exceeding the margin of error (the margin of error adopted in this paper is 0·2√ A +0·0003 A, where A is the total area of the land parcel in m 2 units) decreased by 26–35%. As for the boundary point displacement, the average boundary point offset of the areas was 0·3–4·2 cm. The positions of boundary points could be corrected by small amounts using the proposed coordinate vector correction method, so that the discrepancies between the area formed by boundary points and the registered area could be effectively solved.